Development of a decision support system to preserve Neolissochilus hexagonolepis (McClelland, 1839) in Pelus River, Perak, Malaysia - Che Hussin, Nur Syafiqah (2016)
Over the past decades, water management has become a global issue and the challenges that relate are increasing globally. Malaysia, which is located at the equatorial zone, has abundant of freshwater resources. Despite that, the country faces challenges of water shortage due to anthropogenic activities. In order to maintain river health, river flow is considered as one of the most important factors to be considered. Environmental Flow Assessment (EFA) specifically determines the quantity, quality, and timing flow of water required over time to sustain water body ecosystems and human livelihoods as well as wellbeing that depend on overall ecosystem. However, with the growing complexity and uncertainty of river flows, it is a challenge for stakeholders as they are required to understand its natural diversity in order to preserve and conserve both goods and services. Hence, in this study, a Decision Support System (DSS) by using IF-THEN rule concept is established to assist decision makers to decide the best possible action in order to maintain the optimum flows. The system is developed specifically based on case study area in Pelus River, Perak as it is classified as an altered river due to dam operation that can directly or indirectly affect the environment. The Neolissochilus hexagonolepis (McClelland, 1839) in Pelus River, Perak fulfils all the must-have criteria for a target fish species. The system has three different modules that cover analysis in the aspects of hydrology, hydraulic, and ecology. Module of river classification implements backward chaining process, which aims to identify the problem parameters in the analysis of river classification. The second module applies Multiple Linear Regression analysis to determine the relationship between hydraulic and ecology aspects in river flow analysis. For the third module, the prediction of minimum river flow based on Mean Annual Minimum analysis is conducted. The verification and validation process of the system is conducted in Pelus River, Perak. The system is also verified by the experts in the respective field which involves evaluation on system functioning and user friendliness aspects. In conclusion, this system is absolutely convenient, comprehensive, and could assist better decision making which then become useful tools in solving problems of river management, specifically in Pelus River in order to preserve the target species, N. hexagonolepis.